Feed processing challenges facing the swine industry - De Jong, Jon (Kansas State University, 2015)
Eight experiments using a total of 2,964 finishing pigs and 2,947 feed, phytase, or premix samples were used to determine the effects of: 1) wheat source, particle size and feed form on finishing pig performance; 2) feed form feeding strategies; 3) fine generation from pellets during feed manufacturing and delivery, and 4) thermal stability and shelf life of phytase products. Exp. 1 and 2 evaluated wheat sources, particle size, and diet form for finishing pigs. Fine gound hard red winter wheat fed in meal form improved G:F and nutrient digestibility, whereas wheat ground from ~700 to 250 µ in pelleted diets did not influence growth or carcass traits. Feeding hard red winter wheat improved ADG and ADFI compared with feeding soft white winter wheat. In Exp. 3, pellet feeding regimens were used to evaluate finishing pig performance and stomach morphology. Feeding pelleted diets improved G:F but increased stomach ulceration and pig removals; however, rotating pellets and meal diets provided an intermediate G:F response with fewer stomach ulcers and pig removals. Experiments 4 to 6 investigated fines formation during pelleted feed manufacturing and delivery. Pellet quality worsened as pellets were transported through the feed mill post pelleting and during delivery. Unloading speed or feed line location had little effect on pellet quality. There were significant differences between the fines and pellet nutrient profiles as noted by the increased concentration of ADF, crude fiber, Ca, ether extract, and starch in the fines and decreased CP and P when compared to pellets. In Exp. 7 and 8, the thermal stability and shelf life of 4 commercial phytase products was determined. Increasing conditioning temperatures decreased phytase stability regardless of product. Phytase activity was affected by storage duration, temperature, product form, and phytase source. Pure products stored between 15 and 22˚C were the most stable and premixes were affected by longer storage times and higher temperatures.
Keywords: Phytase; Pelleting; Pellet fines; Feed processing; Wheat; Animal Sciences (0475)